The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.anai.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

School nurse perspectives on school policies for food allergy and anaphylaxis

Abstract: With one-third of school nurses reporting an allergic reaction in the past year, schools use many strategies to minimize allergen exposures and increase anaphylaxis preparedness. Most school nurses favor these policies and acknowledge barriers to implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
0
17
0
4
Order By: Relevance
“…It has been shown that mothers have significantly lower food allergy related quality of life compared to fathers . Second, we probed student and family experiences, but not those of teachers, nurses, and administrators, who may have presented contrasting views . Data from the School Health Policies and Practices Survey, completed by school nurses and administrators, indicate a high level of school engagement in safe food allergy management.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that mothers have significantly lower food allergy related quality of life compared to fathers . Second, we probed student and family experiences, but not those of teachers, nurses, and administrators, who may have presented contrasting views . Data from the School Health Policies and Practices Survey, completed by school nurses and administrators, indicate a high level of school engagement in safe food allergy management.…”
Section: Discussionmentioning
confidence: 99%
“…Foi apontada como medida para melhorar a comunicação, a criação de Programas de conscientização sobre alergia na comunidade, implementando ações conjuntas com as famílias, escolas e profissionais de saúde para garantir treinamento, informação e um melhor gerenciamento da criança alérgica alimentar (Grief, 2016;Kao et al, 2018;Pouessel et al, 2017;Robinson et al, 2017;Sicherer et al, 2017;Tanner & Clarke, 2016;Urrutia-Pereira et al, 2018;Vale et al, 2013Vale et al, , 2015. Outra ação de segurança descrita foi a comunicação com a equipe de nutrição (Pouessel et al, 2017) e com os médicos responsáveis, pois precisam dar orientações aos pacientes e familiares como evitar o contato com os alérgenos e para que saibam reconhecer sinais e sintomas de anafilaxia (Song & Lieberman, 2019).…”
Section: ) Comunicação Efetiva Entre Funcionários E Familiaresunclassified
“…A necessidade de elaborar um Plano de Intervenção para prevenção de riscos na escola com estratégias para evitar exposição aos alérgenos por ingestão acidental, contato, inalação ou até mesmo pela contaminação cruzada, que engloba a transferência de partículas de um alimento ou superfície por meio de utensílios, equipamentos ou pelo próprio manipulador foi sinalizada nas publicações (Cabrera et al, 2017;Kao et al, 2018;Vale et al, 2013).…”
Section: ) Melhorar a Segurança Dos Medicamentos Utilizados Nas Reaçunclassified
See 2 more Smart Citations